Uma abordagem de isometria em sala de aula - Mir, Michel [UNESP] (2014)
This work has as main objective to study the isometries - in the plane and in the space - inside the classroom. Initially is performed a brief historic rescue about the relation between the concepts of isometry and beauty through the ages. Some of isometries have been observed in nature in animals and plants, and works constructed by mens, such as objects, famous architectural works and artworks (paintings and sculptures). We seek to conceptualize and demonstrate the types of isometries in the plane, as well as their compositions, and conceptualize the types of isometries in space. After the theoretical foundation, we describe the realization of activities in the classroom using different types of grids and pictures cut from magazines and newspapers, with the goal of bringing students to identify some sort of isometry. In the end, we present an analysis of how the teaching and learning of isometries are dealt in some official documents of education in Brazil (PCNs, Curriculum of São Paulo and arrays of references SARESP)